(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
Consumption of a diet rich in vegetables significantly enhances overall wellbeing by reducing the risk of various chronic conditions, including cardiovascular diseases, hypertension, hypercholesterolemia, osteoporosis, several types of cancer, chronic obstructive pulmonary disease, respiratory disorders, and mental health issues. The protective effects of vegetables are often attributed to their phytochemical content, which may contribute to anti-inflammatory properties beneficial in managing cardiovascular diseases. However, the precise mechanisms of action of these phytochemicals remain difficult to fully elucidate. Anaemia remains a serious health concern across all age groups—children, adolescents, and adults alike. Jatropha tagorensis, commonly referred to in Northern Nigeria as “Get well soon” or “Kafi likita,” is traditionally used for its antianaemic and antioxidant properties. This study investigated the phytochemical composition and proximate nutrient content of fresh J. tagorensis leaves sourced from farms on the outskirts of Zaria, Kaduna State, Nigeria. Qualitative phytochemical screening was performed using established methods to detect the presence of key bioactive compounds: tannins (Van-Burden and Robinson, 1981), saponins (Obadoni and Ochuko, 2001), flavonoids (Boham and Kocipai-Abyazan, 1994), alkaloids (Harborne, 1973), phenols (Trease and Evans, 1985), and phlobatannins (Sofowora, 1993). The percentage composition obtained was: tannins (0.53%), saponins (0.80%), flavonoids (3.32%), alkaloids (0.67%), phenols (0.31%), and phlobatannins (1.43%). Proximate analysis, conducted using the Association of Official Analytical Chemists (AOAC, 2000) methods, revealed the following composition: dry matter (89.01%), moisture content (5.44%), crude protein (17.75%), lipid (5.36%), crude fibre (5.32%), ash (14.49%), and carbohydrate (51.64%).